PERBANDINGAN KEJADIAN NYERI KEPALA TEGANG OTOT (TENSION TYPE HEADACHE / TTH) ANTARA PENGGUNA KOMPUTER DAN MIKROSKOP PADA PEKERJA - Yusmahenry Galindra; Ade Ricky Harahap (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Computers and microscopes are tools used by workers at PT. NPCB, in the quality control and screening section. When working using the tool within> 4 hours can cause tension headaches in the muscles. This study aims to determine the comparison of the incidence of muscle tension headaches between computer users and microscopes. This type of research is quantitative and analytic with the cross-sectional approach. Respondents are 33 people who use computers and 34 microscopy users at PT. NPCB Batam City in 2019. Computer users and microscope users are measured on their headache scale using the VAS questionnaire. Data were analyzed univariately and bivariate. Bivariate analysis records the frequency distribution of each variable. Bivariate analysis using the chi-square test. From the chi-square test results showed no significant difference in the incidence of muscle tension headaches between computer users and microscope users with a significance value (Pearson value) of 0.957 (p> 0.05). The comparison of the VAS value of Computer and Microscope users is 4.73: 4.41 with a p-value of 0.523. Based on this study it can be concluded that there is no significant difference in the incidence of muscle tension headaches between computer users and microscopes.